Motivational and socio-cognitive determinants of entrepreneurial intention of undergraduates in Malaysia - Hassan, Arif; Al Jubari, Ibrahim Hizam Ali (UNTAR: Tarumanagra University, Indonesia, 2015)
The study proposed to examine the role of basic psychological needs fulfilment in rendering entrepreneurship more attractive and advantageous to university students. Specifically, it aims at integrating Self-Determination Theory (SDT) and Theory of Planned Behaviour (TPB) to better understand entrepreneurial intention. Study used survey research design. Sample consisted of 438 (Males = 166, Females =272) 3rd and 4th year university students from four Public Universities in Malaysia. Standardized instruments were used to measure the constructs. The findings showed that basic psychological needs fulfilment influenced students’ entrepreneurial intention through its proximal attitudinal predictors.